ABS-PoNR: Attribute-Based Signature scheme with Proof of Non-Revocation - Shivani Goel; Mridul Kumar Gupta; Saru Kumari (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In this paper, we introduce a novel Attribute-Based Signature scheme with Proof of Non-Revocation (ABS-PoNR) that enhances security and fine-grained access control in dynamic environments. Our scheme extends traditional attribute-based signatures by incorporating a non-revocation mechanism for attributes and unique user identifiers (UUIDs). It ensures that signatures remain valid only if the signer’s attributes and UUIDs have not been revoked. The proof of non-revocation allows verifiers to check the revocation status without compromising privacy and rejects signature if the proof is invalid or attributes are revoked. Utilizing bilinear pairing-based cryptography, the ABS-PoNR scheme enables efficient and secure attribute-based signing. Our security analysis is based on the Computational Diffie-Hellman (CDH) assumption and proves the unforgeability of the scheme which makes it computationally infeasible to forge valid signatures. We also discuss the efficiency and practical applicability of the ABS-PoNR technique in scenarios requiring dynamic attribute management and frequent updates to access rights. It marks a significant advancement in attribute-based cryptography.